Use of synthesised ultradispersed substances in technological systems - Bodachivska, Larysa Yu. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2024)
Ultrafine calcium carbonate was synthesized by the exchange reaction and carbonation method with crystallite size of 7-44 nm. The size, polymorphic modification, and morphology of the crystallites were confirmed by X-ray diffraction analysis and scanning electron microscopy. The main attention is focused on development of methods for the synthesis of ultrafine calcium carbonate directly at the sites of well depressurization (microcracks) and the basics of technology for eliminating or preventing fluid manifestations in oil and gas wells. Depending on the intensity of gas occurrences, gas migration paths, the size of gas pipeline channels, the location of depressurization areas, thermobaric conditions, as well as the technical and operational condition of wells, it is proposed to perform sealing in one of two effective ways. The first method involves sealing microscopic gas flow channels by transporting highly mobile low-viscosity solutions containing chemical reagents in a colloidal state to the depressurization sites, followed by creating conditions for their reaction and the formation of solid or gel-like sealants. To implement this method, one inverted microemulsion is prepared, the internal phase of which is an aqueous solution with the ionic reagent CaCl2, and the second – with the ionic reagent Na2CO3, which are injected together under stirring by the “jet to jet” method to form CaCO3 crystallites and are pressed by carbon dioxide into the depressurized areas. The second method of sealing microscopic gas flow channels involves transporting a low-viscosity solution containing one of the reagents in a colloidal state and the other reagent in a gaseous state to the depressurization sites, followed by creating conditions for their reaction and the formation of solid or gel-like sealants. The technical result of this method is achieved by the interaction of calcium hydroxide contained in the polar phase of the inverted micelle with carbon dioxide, which is pre-filled into the well. The permeability of CO2 through the membrane-like adsorption-solvent shell of biosynthetic surfactants around the calcium hydroxide facilitates the formation of CaCO3 and the pushing of ultrafine calcium carbonate by carbon dioxide into the gas-fluid channels. The well is treated using the “sliding tamping” method in the repression-depression mode.